2004
DOI: 10.1111/j.1475-3588.2004.00091.x
|View full text |Cite
|
Sign up to set email alerts
|

A Home and School Support Project for Children Excluded from Primary and First Year Secondary School

Abstract: Background:  In the last 10 years the problem of exclusion has reached a crisis point. Research suggests that exclusion is a complex phenomenon that needs involvement from all the involved services such as Health, Education and Social Services. Method:  One hundred and twenty‐four pupils, aged 4–12 years who, through school and social exclusion, were at risk of developing more serious mental health difficulties, were randomly allocated to standard care (n = 62) or standard care plus the new intervention (n = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…We found seven studies (19%) whose description of the baseline equivalence suggested a high-risk. This was found, for instance, in cases where the control group presented higher levels of exclusion than the treatment group and there was not clear mention of adjustment (e.g., Panayiotopoulos & Kerfoot, 2004). Another example concerns the imbalance of one specific type of exclusion: specifically, expulsion and out-of-school exclusion were equivalent in the treatment and the control groups, but display substantial imbalance in the case of inschool exclusion (e.g., Berlanga, 2004).…”
Section: Baseline Equivalence In the Outcome Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…We found seven studies (19%) whose description of the baseline equivalence suggested a high-risk. This was found, for instance, in cases where the control group presented higher levels of exclusion than the treatment group and there was not clear mention of adjustment (e.g., Panayiotopoulos & Kerfoot, 2004). Another example concerns the imbalance of one specific type of exclusion: specifically, expulsion and out-of-school exclusion were equivalent in the treatment and the control groups, but display substantial imbalance in the case of inschool exclusion (e.g., Berlanga, 2004).…”
Section: Baseline Equivalence In the Outcome Measuredmentioning
confidence: 99%
“…We tried to contact authors but it was not possible. We calculate an approximate SE=.013.Presence/absence27) Panayiotopoulos & Kerfoot (2004)Journal article12410Home and School Support Project (HASSP)IndicatedUnknownNo Exclusion T1: M=9.50; SD=14.81; N=62 C1: M=5.11; SD=7.56; N= 62 Post treatment (After three months) T2: M=4.95; SD=13.11; N=61 C2: M=5.51; SD=11.94; N=62Effect size was calculated as the difference between baseline and post treatment. We corrected final calculations by adding the value of pre/post correlation, assumed to be equal .75.Nº days28) Peck (2006)PhD Thesis1050Fifth to eighth gradeStudent Targeted with Opportunities for Prevention (STOP)UnclearUnknownNo Suspension Post‐treatment (unclear number of weeks/months after treatment) T2: 22; N=315 C2: 22; N=321Data was entered into CMA by using a 2x2 table.…”
Section: Tablesmentioning
confidence: 99%
“…Gerner and Wilson (2005) indicated that social acceptance was typically perceived by students as being one of the most important indicators of a successful transition. Besides social adjustment, the change in learning environment, teachers, peers, new subjects and learning style, can all lead to educational and/or psychologically negative outcomes (Eccles and Midley, 1990;Panayiotopoulos and Kerfoot, 2004). The choices about their future that pupils face in secondary school and beyond can be more complicated for young people with SEND because they Findings from a longitudinal study carried out by Aston et al (2005) on young people with special educational needs undergoing the transition process, suggested that the agencies which support all young people in England with transition to higher education and employment are complex and fragmented.…”
Section: Introductionmentioning
confidence: 99%
“…Due to family breakdown and poverty shown in the findings, children may follow their parents' example in the future (Panagiotopoulos & Kerfoot, 2004) or may have fewer opportunities for personal and professional growth. As Parsons (1994) claims, because of this dysfunctional system, troubled children can stay out of the educational network for a long time awaiting support that does not seem to exist.…”
Section: Discussionmentioning
confidence: 79%